The experiences and challenges of Doctoral Education in Public Universities compared - Ocan Johnson; Eton Marus; Akena Francis Adyanga; Natal Ayiga (Goodwood Publishing, 2023)
Purpose: This article’s purpose is to explore the challenges and experiences PhD students in selected Ugandan state universities endure during their studies. Research methodology: The approach of the research focused on three public universities thus; Kabale University, Makerere University, and Gulu University. To explore these challenges, we undertook an extensive literature review of the external supervisors and evaluations of PhD students who attempted to submit their final dissertations. Results: The main findings of the results indicate that due to institutional, individual, and supervisory inefficiency, many students who enroll in their PhD programs at these universities are unable to graduate within the given timeframe. Limitations: The limitations of the study conclude that the problems addressed in this research and the suggestions presented provide the basis for improving university training programs and facilitating students, timely completion of the PhD program. Contribution: In terms of contribution, this research will improve scholarly writing and publication abilities, in addition to increasing the identity of doctoral education in Uganda. Evidently, there is no substantial work exploring the difficulties and challenges faced by PhD students in Uganda. Novelty: it is crucial to remember that when pursuing their PhDs, scholars are not just learning about the research topic, but are also developing fundamental skills in critical thinking, to construct their own knowledge within their own indigenous context, it is essential that they acquire the capacity to assess assertions, and evaluate arguments in a critical manner.